The Role of Non-State Actors in Maritime Diplomacy: International Organizations and NGOs in Resolving Maritime Disputes - Sarjito, Aris (Department of Government Studies, Universitas Syiah Kuala, 2024)
The escalating complexities of maritime disputes necessitate a nuanced examination of the evolving role of non-state actors in maritime diplomacy. This research delves into the conceptualization of non-state actors in international relations, with a primary focus on the roles played by international organizations and non-governmental organizations (NGOs) in resolving maritime disputes. Employing qualitative research methods using secondary data, this study draws on existing literature to analyze the conceptual frameworks, roles of international organizations in conflict resolution, contributions of NGOs to maritime diplomacy, and factors influencing the effectiveness of non-state actors in dispute resolution. Findings illuminate the multifaceted nature of non-state actors, showcasing their diverse contributions to diplomatic efforts, from mediation and conflict prevention to post-conflict reconstruction. This research contributes novel insights by synthesizing existing knowledge on non-state actors in the context of maritime diplomacy and providing a comprehensive understanding of their impact on global and regional maritime governance. The study's findings inform policymakers, scholars, and practitioners engaged in maritime diplomacy, shedding light on the intricate dynamics that shape the effectiveness of non-state actors in addressing maritime challenges.Keywords: conflict resolution, international organizations, maritime diplomacy, NGOs, non-state actors